From theory to textbook: Constructing language materials for young learners - Ken Beatty (Universidad de La Sabana, 2012)
Second language materials for young learners are often deceptive in their simplicity. They appear to be easy to create because their content spans a limited range of grammatical forms and vocabulary. However, beyond the challenging process of selecting such content are the underlying theoretical concepts, methodologies and approaches that inform well-constructed learning materials. This paper outlines considerations that go into creating a textbook series for young learners in terms of views of language learning, the communicative approach, a notional-functional syllabus, comprehensible input and output, task chains, learner-centeredness, the negotiated curriculum, and autonomy.